Hepatitis B Virus Subtype Distribution in Bangladeshi Chronic Carriers (Northern International Medical College Journal, 2018)
Background : Hepatitis B virus (HBV) infection is one of the major global health problems and this virus has many variants that differ from epidemiological distributions, transmission sources, clinical outcomes, diagnostic assays as well as therapeutic responses. HBV was also divided into 9 different subtypes which has distinct geographical distributions and important for the epidemiological studies and vaccine development.Objective : Bangladesh is an intermediate prevalence region for HBV infection, however, very little is known about the incidence of HBV subtypes in circulation. Therefore, we investigated the HBV subtype distribution in Bangladesh.Method : A small cohort was performed on between March 2014 and August 2017 with 172 HBV DNA positive patients from the BSMMU. From them, 29 HBV DNA samples were isolated for sequencing by Sanger method. HBsAg subtypes were determined by identifying of 226 amino acid (aa) positions in the small surface (S) gene.Result : Our study showed that HBV subtype adrq+ was in 17 (58.6%) isolates, ayw3 in 8 (27.5%), ayw2 in 2 (6.9%) and adw2 in 2 (6.9%) isolates.Conclusion : We conclude subtype adrq+ predominant in Bangladesh. This was followed by ayw3, while adw2 and ayw2 were least dominant. Subtype adw2 and adrq+ strains are found to be related with more complication, therefore, patients infected with these HBV strains need to be careful monitoring to assess their clinical outcome in future.Northern International Medical College Journal Vol.9(2) Jan 2018: 286-290